Vitamin D - From the pro-hormone to the biological actions - Craveiro,Vanda (2019)
Vitamin D (calciferol) is a fat-soluble pro-hormone presenting two major forms - vitamin D2 (ergocalciferol) and vitamin D3 (cholecalciferol). Vitamin D2 is obtained via ultraviolet B (UVB) irradiation of ergosterol, a fungi sterol, and vitamin D3 is synthesized in the human/animal skin, after exposure of 7-dehydrocholesterol to UVB radiation. Both forms are produced commercially and found in supplements and in fortified foods. Either from the cutaneous synthesis (D3 ), or from the diet (D2 and D3 ), both vitamins need to be activated, which requires two hydroxylation reactions, one mediated by the 25-hydroxylase and other mediated by the 1α-hydroxylase. Thus, either vitamin D2 or D3 originate the calcitriol. This active metabolite is responsible for biological actions, characterized as genomic, mediated via the vitamin D receptor (VDR) transcriptional effects in the nuclei of target cells, and non-genomic, mediated via the rapid VDR-induced signal transduction pathways on the cell membrane and/or cytoplasm. Besides the endocrine actions of calcitriol (regulation of calcium and phosphorus, with interactions in the kidneys, bones, parathyroid glands, and small intestine), the ubiquitous presence of VDR in the organism contributes to the autocrine and paracrine actions of calcitriol, such as the inhibition of cell proliferation, promotion of cell differentiation (including differentiation of keratinocytes), apoptosis and immune regulation. Also, calcitriol is involved in the preventive and therapeutic action in cancer, auto-immune conditions (including type 1 diabetes), cardiovascular diseases, and infections.